Model Assessment on Cooling Effect of Mangrove and Proboscis Monkey Conservation Area in Tarakan City - Nuzula Elfa Rahma; Yulma Yulma (Center for Journal Management and Publication, 2021)
A conservation area for mangrove forests and proboscis monkeys locates within a dense urban centre in Tarakan city. Its surrounding area has rapidly transformed into condensing urban artificial structures with minimal vegetation cover. The study aims to determine the cooling effect of the conservation area toward its surrounding. The study applies model assessment, which comprises ENVI-MET for simulation of air temperature distribution, and Rayman for PMV (Predicted Mean Vote) calculation to investigate the level of heat stress. The result shows that the mangrove cover has a cooling effect effectively after midnight to 11:00 the subsequent day. Specifically, for the surrounding area, it is confined within an 8-hour window (from 0:00 to 8:00). Within this window, inside the mangrove area, ENVI-METÂ generates significantly lower air temperature, when compared to its surrounding. The mangrove presence correlates to reducing air temperature up to 1.8Â° C. The cooling effect also extends to its surrounding with a limited radius (approximately 10 m). However, PMV calculation implies that there is no significant improvement in thermal comfort as a result of the mangrove presence. The results may not adequately reflect the reality in the field. Further research to calibrate PMV measurement that involves human monitoring is required to validate the findings.